Using Theory-Based Test Construction to Develop a New Curriculum-Based Measurement for Sentence Reading Comprehension - Jungjohann, Jana; DeVries, Jeffrey M.; Mühling, Andreas; Gebhardt, Markus (Frontiers in Education, 2018)
Reading comprehension at sentence level is a core component in the students’ comprehension development, but there is a lack of comprehension assessments at the sentence level, which respect the theory of reading comprehension. In this article, a new web-based sentence-comprehension assessment for German primary school students is developed and evaluated using a curriculum-based measurement (CBM) framework. The test focuses on sentence level reading comprehension as an intermediary between word and text comprehension. The construction builds upon the theory of reading comprehension using CBM-Maze techniques. It is consistent on all tasks and contains different syntactic and semantic structures within the items. This paper presents the test development, a description of the item performance, an analysis of its factor structure, and tests of measurement invariance and group comparisons (i.e., across gender, immigration background, over two measurement points, and the presence of special educational needs; SEN). Third grade students (n = 761) with and without SEN finished two CBM tests over three weeks. Results reveal that items had good technical adequacy, the constructed test is unidimensional, and it is valid for students both with and without SEN. Similarly, it is valid for both sexes, and results are valid across both measurement points. We discuss our method for creating a unidimensional test based on multiple item difficulties and make recommendations for future test construction.